Exploration of Madura Local Wisdom as a Support for Ethnoscience-Oriented Madura Tourism Database - Yasir, Mochammad (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2023)
The purpose of this research is to identify and classify the types of ethnoscience-ecotourism on Madura Island, and examine the supporting and inhibiting factors. This study employs a qualitative descriptive research design and is conducted in the regencies of Bangkalan, Sampang, Pamekasan, and Sumenep. The research instruments include the researchers themselves, interview guides, and other supporting materials, whereas the data sources are primary and secondary data obtained through observation, interviews, and documentation. utilizing interactive analytic techniques to analyze research data Huberman and Miles. The results showed that the types of Madurese local wisdom with the concept of ethnoscience-ecotourism were Aer Mata Ebuh Arosbaya Bangkalan Market, Lon Malang Sampang Beach, Pamekasan Salt Education, and the Sumenep Palace Museum; The clustering of Madurese local wisdom as an ethnoscience-based tourist object that has been carried out shows that the Aer Mata Ebuh Arosbaya Bangkalan Islamic Boarding School is included in the type of religious tourism, Lon Malang Sampang Beach is of the nature and halal syari'ah tourism type, Pamekasan Salt Tourism is of the educational tour type, and the Sumenep Palace Museum type of heritage tourism. Factors supporting the development of ethnoscience-ecotourism in Madura are the concept of place, certain points as references, history in Madura and natural landscapes which are the main attraction for tourists. The inhibiting factors for the development of ethnoscience-ecotourism in Madura are the absence of the participation of the closest government apparatus (Village/POKDARWIS), the uncoordinated route network for the Madura tour network, inadequate transportation routes.